Kualitas Mutu Sabun Cair Organik Berbahan Dasar Minyak Jarak Dan Soda Qie - Priskalia Inge Sriwening; Maria Mita Susanti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Liquid soap is an important need for many because this soap can clean the dirt that sticks to the skin. Formation of soap due to the process of saponification. Saponification process there needs to be oil and bases as the main raw materials it's castor oil as an oil phase. The base used in the manufacture of liquid soap is Soda qie, which is extracted from the peel of the boar. Sodium carbonate was 26.27%, and sodium hydroxide was 4.37%. The purpose of this study was to see the quality of the cast-based liquid soap and the ashes of the husk skin including organoleptic tests, pH, foam power, free alkali, and viscosity. The kind of research used was explorative research with comparing results here. Liquid soap quality testing methods based on castor oil and soda qie include organoleptic tests, pH tests, tests Viscosity, foam power test, free alkali test, and identification of potassium Soda die. The results are descriptive and presented in the form of a chart. The results of the quality liquid soap are based on castor oil and soda qie. Did not meet the quality of SNI 06-4085-1996, received power test foam at 2,23cm, pH test at 9,9 and viscosity 1193. The alkali tests are free not met quality requirements determined by results of 0,75%.